2019
DOI: 10.4172/clinical-practice.1000451
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality among patients with chronic obstructive pulmonary disease at a university hospital in Egypt

Abstract: Background: Disturbed sleep is a common complaint in patients with the Chronic Obstructive pulmonary Disease (COPD). Moreover, the factors affecting sleep quality of those patients remain unclear. The aim of this study: was to assess sleep quality among patients with the chronic obstructive pulmonary disease. Material and Methods: A descriptive exploratory design was utilized and conducted at the intermediate respiratory care unit at Mansoura university hospital including a convenient sample of 60 patients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Concerning the relation between characteristics of the studied elderly patients and sleep quality, there was a significant relation found between age and quality of sleep. This is congruent with a study finished in Egypt by Khalil et al, (2019) 21 . In contrast, Geiger et al, (2015) 53 initiate that there was a statistically significant negative relationship between quality of sleep and age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Concerning the relation between characteristics of the studied elderly patients and sleep quality, there was a significant relation found between age and quality of sleep. This is congruent with a study finished in Egypt by Khalil et al, (2019) 21 . In contrast, Geiger et al, (2015) 53 initiate that there was a statistically significant negative relationship between quality of sleep and age.…”
Section: Discussionsupporting
confidence: 93%
“…In relation to marital status, the current study revealed that greatest of the studied elderly patients were marital. This result in the same line with a study prepared in Egypt by Khalil and Mostafa., (2019) 21 . Also, the present study revealed that illiteracy was high prevailing among the studied elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, daily life habits as daytime naps and smoking. 10 Malhotra et al, in there article concluded that polysomnographic features in COPD are a consequence of sleep-induced respiratory loads. Patients with COPD may respond to increased respiratory loads with marked sleep disturbances or, alternatively, they may have minimal sleep disturbance but a highly abnormal breathing pattern with or without severe alterations in gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a serious global health problem [1]. Different studies proposed that more than 75% of patients with COPD may have nocturnal symptoms and sleep disturbances in the form of prolonged sleep latency, arousals, and frequent insomnias [2], resulting in decrease in patient's activity during daytime associated with more severe disease and frequent exacerbations [3].…”
Section: Introductionmentioning
confidence: 99%